(untitled) (Global Journal of Science Frontier Research, 2016)
Radial Schrodinger equation for the doubly An-Harmonic oscillator is considered and the transformation to Bi-Confluent equation done in 13 are considered Super-symmetry method of factorization is applied to the transformed equation in obtaining solutions of the Schrodinger equation Partner potentials and super-potentials are obtained